2008
DOI: 10.1249/mss.0b013e318161aa99
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Leg Blood Flow during Submaximal Exercise in Type 2 Diabetes

Abstract: These findings suggest that impaired femoral arterial blood flow, an indirect marker of muscle perfusion, affects low-intensity exercise performance in patients with type 2 diabetes. However, because of lower exercising stroke volume, we propose that femoral arterial blood flow and, possibly, cardiac output, limit V O(2 max) in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 26 publications
5
80
1
Order By: Relevance
“…Observations of slowed oxygen kinetics at the onset of exercise and decreased skeletal muscle blood flow during exercise in patients with T2D (13,70,76,129,152) may be explained, in part, by decreased capillary perfusion. In a series of studies using the Goto-Kakizaki T2D rat model, Padilla and colleagues (118,119) demonstrated that reductions in the microvascular partial pressure of oxygen at rest and during skeletal muscle contraction may owe to reduced capillary perfusion (i.e., reduced percentage of capillaries perfused with moving red blood cells, lower red blood cell flux, and decreased O 2 delivery per unit of muscle).…”
Section: Ex Smooth Muscle and Capillary Function And Vascular Remodmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of slowed oxygen kinetics at the onset of exercise and decreased skeletal muscle blood flow during exercise in patients with T2D (13,70,76,129,152) may be explained, in part, by decreased capillary perfusion. In a series of studies using the Goto-Kakizaki T2D rat model, Padilla and colleagues (118,119) demonstrated that reductions in the microvascular partial pressure of oxygen at rest and during skeletal muscle contraction may owe to reduced capillary perfusion (i.e., reduced percentage of capillaries perfused with moving red blood cells, lower red blood cell flux, and decreased O 2 delivery per unit of muscle).…”
Section: Ex Smooth Muscle and Capillary Function And Vascular Remodmentioning
confidence: 99%
“…physical activity is associated with an increased incidence of cardiovascular events, microvascular complications, and allcause mortality (17), and a decreased aerobic capacity is associated with the presence of neuropathy, retinopathy, or nephropathy (48). Likewise, in humans, T2D is associated with slowed oxygen kinetics at the onset of exercise (13,129) and attenuated skeletal muscle blood flow responses to exercise (70,76,152), as well as glucose intolerance (19a). Importantly, each of the aforementioned conditions (neuropathy, retinopathy, nephropathy, exercise intolerance, and glucose intolerance) is caused, in part, by microvascular dysfunction.…”
mentioning
confidence: 99%
“…Blood pressure was measured during pedaling and at the end of MRI measurements. Ventricular volumes were calculated from steady-state free-precession cine acquisitions, using six parallel short-axis acquisitions and three long-axis acquisitions at 08, 608, and 1208, as previously described (26,29,30). These data were analyzed by members of the research team who were blinded to subject details and group allocation, using three-dimensional volumetric modeling software (Cardiac Image Modeller; Auckland MRI Research Group, Auckland, New Zealand).…”
Section: Cardiac Mrimentioning
confidence: 99%
“…It is thought that chronic exposure to these excess metabolites may lead to downregulation of metaboreceptors or decrease their sensitivity 11) . It is therefore possible that this chronic exposure to metabolites also occurs in patients with type 2 DM, as they are known to have reduced blood flow to the muscles both at rest 13) and during exercise 14,15) . Evidence in support of this mechanism is that administration of capsaicin, a transient receptor potential vanilloid 1 (TRPV1), into a limb artery causes selective activation of metabolically sensitive afferent fibers involved in the muscle metaboreflex, and reduced capsaicin-induced pressor responses in a mouse model of type 2 DM was shown to be closely related to reduced vascular TRPV1 expression 16) .…”
Section: Discussionmentioning
confidence: 99%